All together now: regulation of the iron deficiency response. (15th January 2021) - Riaz, Nabila; Guerinot, Mary Lou
Abstract: Iron (Fe) is one of the essential micronutrients required by both plants and animals. In humans, Fe deficiency causes anemia, the most prevalent nutritional disorder. Most people rely on plant-based foods as their major Fe source, but plants are a poor source of dietary Fe. Therefore, there is a critical need to better understand the mechanisms involved in the uptake and trafficking of Fe and how plants adapt to Fe deficiency. Fe participates in key cellular functions such as photosynthesis and respiration. Perturbations of Fe uptake, transport, or storage affect plant growth as well as crop yield and plant product quality. Excess Fe has toxic effects due to its high redox activity. Plants, therefore, tightly regulate Fe uptake, distribution, and allocation. Here, we review the regulatory mechanisms involved at the transcriptional and post-translational levels that are critical to prevent Fe uptake except when plants experience Fe deficiency. We discuss the key regulatory network of basic helix–loop–helix (bHLH) transcription factors, including FIT, subgroup Ib, subgroup IVc, and URI (bHLH121), crucial for regulating Fe uptake in Arabidopsis thaliana . Furthermore, we describe the regulators of these transcription factors that either activate or inhibit their function, ensuring optimal Fe uptake that is essential for plant growth. Abstract : A network of bHLH transcription factors and the proteins that regulate them ensures iron uptake when iron is limiting and prevents accumulation of excess iron when supplies are adequate.